Development of Augmented Reality (AR) to Support Learning in The Introduction to Information Technology (PTI) Course: A Case Study at Darma Persada University - Ferdi Maulana Akbar; Adam Arif Budiman (Prodi Teknologi Informasi Universitas Darma Persada, 2026)
Advances in Augmented Reality (AR) technology offer significant potential for enhancing learning in the Introduction to Information Technology (PTI) course at Darma Persada University, particularly regarding computer hardware concepts that are difficult to comprehend abstractly through conventional textbooks and slides. This study developed a marker-based AR application aligned with the Cisco IT Essentials curriculum, employing the Multimedia Development Life Cycle (MDLC) methodology. The application was built using Unity3D, Vuforia, Blender, and Visual Studio, presenting interactive 3D models, instructional videos, graded quizzes, volume controls, and marker guides distributed via Google Drive. Black-box testing confirmed successful operation on Android devices, and user testing involving 13 respondents demonstrated positive responses regarding ease of use and improved comprehension of the subject matter. The overall average rating was 3.63 out of 5. This application serves as an effective alternative interactive learning medium for the PTI course.